FLT3-ITD measurable residual disease from the QuANTUM-First trial - Levis, Mark J; Erba, Harry P; Montesinos, Pau; Kim, Hee-Je; Vrhovac, Radovan; Patkowska, Elzbieta; Zak, Pavel; Wang, Po-Nan; Connolly Rohrbach, Jaime E; Chang, Ken; Liu, Li; Mostafa Kamel, Yasser; et al. (Blood advances, 2025)
QuANTUM-First was a randomized trial that demonstrated that the addition of quizartinib, a potent and selective FLT3 inhibitor, to induction and consolidation chemotherapy, followed by monotherapy maintenance, improved the survival for patients with newly diagnosed FLT3-ITD (FMS-like tyrosine kinase 3‒internal tandem duplication)--mutated acute myeloid leukemia (AML). We conducted a post-hoc analysis of the trial data focusing on measurable residual disease (MRD) as assayed using an amplicon-based next-generation sequencing assay and on the impact of molecular biomarkers such as FLT3-ITD insertion length and co-mutations. This is the first prospective, randomized trial of a FLT3 inhibitor in newly diagnosed patients in which FLT3-ITD MRD data were collected throughout therapy. We established that quizartinib induces deeper remissions with respect to FLT3-ITD MRD vs placebo, and that the amount of MRD at the completion of induction correlates with relapse and survival. We found that longer FLT3-ITD insertion mutations correlated with worse outcome, quizartinib was beneficial irrespective of insertion mutation length, and the FLT3-ITD MRD assay was more sensitive when bone marrow was used vs peripheral blood. Regardless of the presence of NPM1 co-mutation, quizartinib increased the rates of MRD-negative patients at the end of induction vs placebo. Finally, comparison of the FLT3-ITD mutation length between the polymerase chain reaction (PCR) with capillary electrophoresis assay obtained at screening and the PCR next-generation sequencing MRD assay performed at the end of induction showed a 96.2% concordance with the exact ITD length. This trial was registered at www.ClinicalTrials.gov as NCT02668653.